Definicje kapitału ludzkiego w ujęciu porównawczym: Definitions of human capital - a comparative and critical approach - Samul, Joanna (Management and Administration Journal, 2021)
Literature often uses terms such as resources, assets, equity in relation to employees interchangeably. Both in Polish and foreign literature, there is no clear definition of these concepts and no precise identification of differences between them. Many of the authors claim that these differences go much deeper than just in the realm of language. There are also authors who are unaware of the difference in these definitions, using them as synonyms. Therefore, the following analysis is an attempt to introduce and organize some issues concerning the definition of human capital and the terms associated with it.